1989
DOI: 10.1063/1.102388
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromic sputter-deposited vanadium oxyfluoride coatings with low luminous absorptance

Abstract: Thin films of VOxFy were made by rf magnetron sputtering of V in Ar+O2+CF4. They were analyzed by Rutherford backscattering spectrometry and transmission electron microscopy. Optical and electrical properties changed within narrow temperature ranges. These results resemble those of thermochromic VO2, although VOxFy has significantly enhanced transmittance, lowered conductance, and marginally depressed switching temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…13 The luminous transmittance can be boosted by magnesium substitution [14][15] and by fluorination. 16 The metal-insulator transition can be influenced by a variety of external parameters, and recent work have considered the effects of strain [17][18][19] and lattice misfit with the substrate, 20,21 electric field or current activation, [22][23][24][25][26][27][28][29][30][31] light irradiation, [32][33][34][35][36][37][38] ion bombardment, 39,40 and gaseous ambience. 41 Considering the wealth of possibilities to modulate the properties of VO 2 -based thin films, it is not surprising that they are discussed for a vast number of applications such as thermochromic "smart" windows for energy efficient buildings, [42][43][44][45][46][47][48][49][50] variable-thermal-emittance surfaces for thermal radiation control, 51 oscillators and switches in (opto)electronics, 25,26,34,52,53 transistors of different types, <...>…”
Section: Introductionmentioning
confidence: 99%
“…13 The luminous transmittance can be boosted by magnesium substitution [14][15] and by fluorination. 16 The metal-insulator transition can be influenced by a variety of external parameters, and recent work have considered the effects of strain [17][18][19] and lattice misfit with the substrate, 20,21 electric field or current activation, [22][23][24][25][26][27][28][29][30][31] light irradiation, [32][33][34][35][36][37][38] ion bombardment, 39,40 and gaseous ambience. 41 Considering the wealth of possibilities to modulate the properties of VO 2 -based thin films, it is not surprising that they are discussed for a vast number of applications such as thermochromic "smart" windows for energy efficient buildings, [42][43][44][45][46][47][48][49][50] variable-thermal-emittance surfaces for thermal radiation control, 51 oscillators and switches in (opto)electronics, 25,26,34,52,53 transistors of different types, <...>…”
Section: Introductionmentioning
confidence: 99%
“…10 Fluorine doping is another way to enhance T lum . [26][27][28][29] Furthermore, antireflection (AR) coatings are able to improve T lum and ΔT sol , and especially good properties have been reported for five-layer coatings of alternating TiO 2 and VO 2 . 2,3 Recent modeling studies on "nanothermochromics" 4,5 have shown that VO 2 nanoparticles can offer significantly higher values of T lum and ΔT sol than films, and these new possibilities have led to a burst of research on such nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 11 indicates that T lum is increased from 39% to 51% as the amount of Mg goes from zero to 7.2%. Band-gap widening can be accomplished also by adding other alkaline earth metals [83], zinc [88] or terbium [89], or by replacing some of the oxygen with fluorine [90][91][92]. zero to 7.2%.…”
Section: Towards Vo2-based Thin Films For Glazingsmentioning
confidence: 99%